Warisan Tak Tergantikan: Mengapa Ebeg Purbalingga Perlu Dilestarikan? - Fauzah, Titi Isnaini; Maknun, Moch. Lukluil; Masfiah, Umi; Hemafitria, Hemafitria (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
Traditional art is an irreplaceable heritage because it contains various noble values, identity markers, and means of connecting with the divine. However, maintaining this heritage is not easy so that it tends to be abandoned by its heirs. This study traces the reasons for maintaining traditional folk art in society by taking the case of Ebeg performing arts in Purbalingga Regency. This study analyzes the social interaction behind the preservation of Ebeg art using the theory of symbolic interactionism which looks at the meaning of symbols given by society to the art to influence its preservation. Data collection was carried out through observation, in-depth interviews, and document reviews, which were then analyzed hermeneutically. The results of the study revealed that Ebeg performing arts actually contain noble values aligned with religious education, such as faith, brotherhood, moderation, and patriotism. The inheritance of Ebeg art on the one hand has been supported by The Purbalingga Regency Government in the form of funding and various preservation initiatives. On the other hand, the inheritance of this art is hampered by the perception of illegality, assumptions of negative influences, lack of financial support from the public, poor public understanding, lack of human resources and infrastructure, as well as a decline in art lovers. The results of this study imply that traditional arts require more than government alone. More than that, the community that supports them must be aware of the importance of preserving cultural heritage. One effort to increase awareness is by the harmony between traditional arts and the noble values of religion, and this emphasizes the novelty of the article.